Programmes and Strategies Targeting Gender and Poverty Reduction in South Africa: A Case Study of Three service Departments - Sithabile Ntombela; Harsha Dayal``' (African Journal of Governance and Development, 2011)
This article emanates from a broader research project that sought to explore ‘new models’ and innovative ways of thinking and dealing with poverty. Using an interpretive research paradigm and multiple case studies, this article seeks to establish if a common understanding of poverty exists within government departments. A case study of three national departments was identified for the enquiry. One of the critical questions that the study wanted to answer is: How do these departments conceptualize and address the impact of poverty? Findings show that there is an aggregated understanding of poverty within departments and they also indicate that poverty intersects with gender. This article concludes that although South Africa has made significant strides in entrenching equality in the Constitution, institutions of the state and in policy documents, gender inequalities in all aspects of life continue to negatively impact on the quality of women’s lives